KAJIAN TEKNIS INTEGRASI PHOTOVOLTAIC PADA PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO (PLTMH) KALI JARI UNTUK MENGATASI KEBUTUHAN DAYA PELANGGAN - Siagian, Alfandri; Utomo, Teguh; Hasanah, Rini Nur (Jurnal Mahasiswa TEUB, 2024)
Currently, the Kali Jari MHPP located in Gandusari district of Blitar has supplied as many as 28 customers with a maximum power on an installed load of 6.16 kVA. As time goes by, the number of residents in this village will increase. It is estimated that by 2050, there will be 58 customers that will be supplied by the PLTMH Kali Jari with a maximum power at installed load of 12.76 kVA. Therefore, it is necessary to carry out studies to make power additions to the installed capacity. Using a renewable energy source, the intensity of abundant solar radiation, the addition of power to the installed capacity can be achieved by using the hybrid Kali Jari MHPP system with a photovoltaic system. To meet the power shortage, the photovoltaic system is designed with other supporting components. The design of this photovoltaic system uses a module with a capacity of 300 Wp of 15 pieces, 48 V 100 Ah batteries of 4 pieces, Battery Control Regulator (BCR) with a maximum current of 70 A of 1 pieces, and a 3 phase inverter of 8 kW of 1 piece. Keywoards: Renewable Energy, MHPP, Photovoltaic, Hybrid System.